2009
DOI: 10.1038/sc.2009.60
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury, coping and psychological adjustment: a literature review

Abstract: Objectives: This paper reviews the literature concerning psychological adjustment to spinal cord injury, focusing on the recent methodological developments and new directions in research. Method: Several literature reviews using the search terms Spinal Cord Injury, Paraplegia, Coping and Adjustment were undertaken using the databases in Pubmed, Medline and Embase. The papers that were published from 2001 onwards, written in English and used a sample of adults were included. Results: The literature reviewed len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 18 publications
5
62
0
3
Order By: Relevance
“…Furthermore, social skills, locus of control and coping, which are psychological resources, have not been considered, because current reviews summarizing findings about these factors have been published in SCI. [18][19][20] It is important to note that coping was only mentioned if it was associated with one of the psychological resources, which we have included. Consequently, the results of this review do not represent the whole picture of current knowledge on coping in SCI.…”
Section: Psychological Resources In Sci C Peter Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, social skills, locus of control and coping, which are psychological resources, have not been considered, because current reviews summarizing findings about these factors have been published in SCI. [18][19][20] It is important to note that coping was only mentioned if it was associated with one of the psychological resources, which we have included. Consequently, the results of this review do not represent the whole picture of current knowledge on coping in SCI.…”
Section: Psychological Resources In Sci C Peter Et Almentioning
confidence: 99%
“…Current reviews in SCI have examined adjustment outcomes such as mental health and quality of life. [5][6][7]18 In addition, external resources such as social support, 19 and internal psychological resources such as locus of control 20 and coping style 18 have been implicated in adjustment outcomes but because of the unaccounted variance, there are perhaps a range of other psychological resources that could be contributing. A systematic overview of psychological resources in SCI does not exist yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 To date, three narrative reviews have surveyed psychological determinants of QOL in persons with SCI. [6][7][8] The first review in 1999 covered a wide array of social and psychological factors in persons with SCI, yet did not extensively address the relationships between psychological factors and QOL. 6 The second review in 2001 focused on appraisals and coping, but concluded that it remains to be determined 'to what extent other variables add to the prediction of emotional adjustment to SCI' (Galwin and Godfrey, 7 p 624).…”
Section: Introductionmentioning
confidence: 99%
“…6 The second review in 2001 focused on appraisals and coping, but concluded that it remains to be determined 'to what extent other variables add to the prediction of emotional adjustment to SCI' (Galwin and Godfrey, 7 p 624). A recent review in 2009 expanded upon the role of coping and appraisals in adjustment to SCI, and provided evidence for the importance of self-efficacy, social cognition, sense of coherence, purpose 8 in life and locus of control (LOC) in the QOL of persons with SCI. Each of these factors was only briefly discussed, however, and the findings of different studies were not compared.…”
Section: Introductionmentioning
confidence: 99%